Method for recovering carbon fiber
The method of immersing CFRP in an acidic solution and then in a foamable alkaline solution addresses the issue of fiber damage in conventional recycling methods, resulting in high-quality recycled carbon fibers with enhanced mechanical properties.
Patent Information
- Application Number
- JP2023150781
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Filing Date
- 2023-09-19
- Publication Date
- 2025-04-01
AI Technical Summary
Conventional methods for recycling carbon fibers from carbon fiber reinforced plastics (CFRP) using high concentration alkaline solutions often damage the fibers, leading to deterioration and reduced quality of the recycled carbon fibers.
A method involving immersion of CFRP in an acidic aqueous solution followed by treatment in an expanded alkaline aqueous solution with foamability, which helps in removing resin content without causing significant damage to the carbon fibers.
This method effectively suppresses damage to recycled carbon fibers, allowing for the recovery of high-quality carbon fibers with improved mechanical properties, such as tensile strength, compared to virgin carbon fibers.
Smart Images

Figure 2025043477000007 
Figure 2025043477000008 
Figure 2025043477000009
Abstract
Description
[Technical field]
[0001] The present invention relates to a method for recovering carbon fibers from carbon fiber reinforced plastics. [Background technology]
[0002] As a method for recycling carbon fibers from waste carbon fiber reinforced plastics, a method is known in which a carbon fiber composite material is immersed in an acidic aqueous solution such as a 6 M nitric acid aqueous solution, and then immersed in an alkaline aqueous solution such as a 2.5 M sodium hydroxide aqueous solution (Patent Document 1). [Prior art documents] [Patent documents]
[0003] [Patent Document 1] JP 2019-136932 A Summary of the Invention [Problem to be solved by the invention]
[0004] However, in the above conventional recycling methods, an alkaline aqueous solution having a high concentration, preferably about 0.1 to 10 M, is used, which causes damage to the recycled carbon fibers, resulting in degradation of the recycled carbon fibers.
[0005] The problem to be solved by the present invention is to provide a method for recovering carbon fibers that can suppress damage to recycled carbon fibers. [Means for solving the problem]
[0006] The present invention solves the above-mentioned problems by immersing a carbon fiber reinforced plastic in an acidic aqueous solution, and then immersing the treated product in an alkaline aqueous solution having foaming properties. Effect of the Invention
[0007] According to the present invention, damage to recycled carbon fibers can be suppressed. [Brief description of the drawings]
[0008] [Figure 1A] FIG. 1 is a diagram showing a method for preparing a sample from waste carbon fiber reinforced plastic parts for automobiles. [Figure 1B] FIG. 1 is a diagram showing a method for treating a sample with an acidic aqueous solution. [Figure 1C] FIG. 1 is a diagram showing a method for treating a sample with an alkaline aqueous solution. [Figure 1D] FIG. 1 illustrates a method for recovering carbon fibers from treated samples. [Figure 2A] 1 is a SEM photograph showing the recycled carbon fiber of Comparative Example 1. [Figure 2B] 1 is a SEM photograph showing the recycled carbon fiber of Example 4. [Figure 2C] 1 is a SEM photograph showing the recycled carbon fiber of Example 10. [Diagram 3] FIG. 1 is a diagram showing the bending strength and bending modulus of a carbon fiber reinforced plastic (vCFRP) made of virgin carbon fiber and a carbon fiber reinforced plastic (rCFRP) made of recycled carbon fiber. [Figure 4] FIG. 1 is a diagram showing the tensile strength and tensile modulus of a carbon fiber reinforced plastic (vCFRP) made of virgin carbon fiber and a carbon fiber reinforced plastic (rCFRP) made of recycled carbon fiber. [Diagram 5] FIG. 1 shows the interfacial shear strength of virgin carbon fiber (vCF) and recycled carbon fiber (rCF). [Figure 6] FIG. 1 is a diagram showing the tensile strength of virgin carbon fiber (vCF) and recycled carbon fiber (rCF). [Figure 7] TEM images showing the cross sections of virgin carbon fiber (vCF) and recycled carbon fiber (rCF). [Figure 8] FIG. 1 shows EDX mapping of voids observed in the fiber cross sections of virgin carbon fiber (vCF) and recycled carbon fiber (rCF). [Figure 9]FIG. 1 is a diagram showing the area ratio of the G1 peak to the D1 peak in the Raman spectrum of a virgin carbon fiber (vCF) and a recycled carbon fiber (rCF) in Raman spectroscopy. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0009] The embodiments of the present invention are a method for recovering carbon fibers from waste carbon fiber reinforced plastics (CFRP), and a method for producing carbon fiber reinforced plastics by using recycled carbon fibers recovered by the carbon fiber recovery method. Hereinafter, an embodiment for carrying out the present invention will be described with reference to the drawings. In this specification and claims, when a range of numerical values is indicated as "x1 to x2", it includes both the numerical values x1 and x2 unless otherwise specified.
[0010] <Method of recovering carbon fiber> The carbon fiber recovery method of the present embodiment includes a first treatment step of immersing a carbon fiber reinforced plastic in an acidic aqueous solution to dissolve at least a portion of the resin content of the carbon fiber reinforced plastic, and a second treatment step of immersing the treated product from the first treatment step in an alkaline aqueous solution having foaming properties to dissolve at least a portion of the resin content of the treated product.
[0011] The carbon fiber reinforced plastic from which the carbon fibers are recovered is not particularly limited, but is preferably waste material, scrap material, or other carbon fiber reinforced plastic that is no longer in use. Carbon fiber is difficult to incinerate because of its highly graphitized structure, and is disposed of in landfills as industrial waste. However, carbon fiber disposed of in landfills is not biodegradable, and therefore becomes a causative substance of marine plastic pollution. Therefore, by recovering and regenerating carbon fiber from such waste material and scrap material, the amount of waste material and scrap material disposed of in landfills can be reduced, which contributes to the suppression of marine plastic pollution.
[0012] The acidic aqueous solution used in the first treatment step is not particularly limited, and an organic acid, an inorganic acid, or a mixture thereof can be used as the acid. Examples of organic acids include formic acid, acetic acid, and citric acid, and examples of inorganic acids include nitric acid, sulfuric acid, hydrochloric acid, and phosphoric acid. The acidic aqueous solution used in the first treatment step can be appropriately determined in consideration of the type of carbon fiber reinforced plastic to be treated and the treatment conditions (mainly the treatment temperature and time). From the viewpoint of the solubility of the resin content contained in the carbon fiber reinforced plastic, it is preferable to use at least one of nitric acid and sulfuric acid, which are inexpensive and easily available.
[0013] The concentration of the acid in the acidic aqueous solution used in the first treatment step can be appropriately determined in consideration of the type of acid, the type of carbon fiber reinforced plastic, the dissolution temperature, the dissolution time, etc. Although not particularly limited, the concentration of the acid in the acidic aqueous solution used in the first treatment step can be in the range of 0.01 to 10 M (mol / l, the same applies below), and the temperature of the acidic aqueous solution can be in the range of 10 to 100° C. As an example of the first treatment step, it is preferable to immerse the carbon fiber reinforced plastic in a nitric acid aqueous solution having a temperature of 60° C. to 80° C. and a concentration of 4 to 8 M for 8 hours or more.
[0014] The foamable alkaline aqueous solution used in the second treatment step is not particularly limited, but examples of the alkali include carbonates and hydrogen carbonates of alkali metals, and carbonates and hydrogen carbonates of alkaline earth metals. Examples of the alkali metal include lithium, sodium, potassium, etc., and examples of the alkaline earth metal include beryllium, magnesium, calcium, etc. Among these, it is more preferable that the aqueous solution contains at least one of carbonates of alkali metals and hydrogen carbonates of alkali metals, and it is most preferable that the aqueous solution contains at least one of sodium carbonate and sodium hydrogen carbonate.
[0015] The foaming aqueous alkaline solution used in the second treatment step is not particularly limited, but is more preferably an aqueous sodium carbonate solution or an aqueous sodium hydrogen carbonate solution having a concentration of 0.005 to 0.1 M. The aqueous alkaline solution of the present embodiment has foaming properties, and therefore in addition to the resin removal effect of the alkali, it also has the effect of physically peeling and removing the resin from the surface of the carbon fiber by the foaming action in the aqueous solution. Therefore, even with an aqueous alkaline solution having a low concentration of about 0.005 to 0.1 M, carbon fibers without any resin residue can be recovered in a short time.
[0016] As an example of the second treatment step, it is preferable to immerse the treated product from the first treatment step in an aqueous sodium carbonate or sodium hydrogen carbonate solution having a concentration of 0.005 to 0.1 M at a temperature of 60 to 80° C. for 1 to 120 minutes.
[0017] The aqueous alkaline solution having foaming properties used in the second treatment step may be an aqueous solution of the above-mentioned alkali carbonate or alkali hydrogencarbonate alone, but may contain a foaming agent to further promote the foaming action of these. The foaming agent contained in the aqueous alkaline solution in the second treatment step is not particularly limited, but preferably contains at least one of a nonionic surfactant and an anionic surfactant.
[0018] Although not particularly limited, the anionic surfactant used as the foaming agent preferably contains at least one of carboxylates, sulfonates, sulfates, and phosphates, and the nonionic surfactant used as the foaming agent preferably contains at least one of polyethylene glycol and other polyhydric alcohols.
[0019] The foaming agent used in the second treatment step is not particularly limited, but may be contained in an amount of 0.05 to 5% by weight, preferably 0.1 to 1.0% by weight, relative to the alkaline aqueous solution.
[0020] <<Method for manufacturing carbon fiber reinforced plastic using recycled carbon fiber>> The carbon fiber recovery method described above recovers carbon fibers having improved properties such as tensile strength compared to virgin carbon fibers. In this specification and the like, the pure carbon fibers used in carbon fiber reinforced plastics before recovery are referred to as virgin carbon fibers, and the recovered carbon fibers are referred to as recycled carbon fibers.
[0021] Using this recycled carbon fiber, carbon fiber reinforced plastic can be manufactured. In particular, the recycled carbon fiber (single fiber) used in this embodiment has higher mechanical properties such as tensile strength than virgin carbon fiber as described later, so that it is possible to obtain carbon fiber reinforced plastic having higher bending strength, tensile strength, and interfacial shear strength than carbon fiber reinforced plastic using virgin carbon fiber. Note that a method for manufacturing carbon fiber reinforced plastic using recycled carbon fiber can be used as is to directly use a known method for manufacturing carbon fiber reinforced plastic. Carbon fiber reinforced plastic can be manufactured by either a method of manufacturing a carbon fiber sheet and then compounding resin, or a method of mixing resin and carbon fiber and then forming into a sheet.
[0022] As described above, the carbon fiber recovery method of this embodiment includes a first treatment step of immersing a carbon fiber reinforced plastic in an acidic aqueous solution to elute at least a part of the resin content of the carbon fiber reinforced plastic, and a second treatment step of immersing the treated product in an alkaline aqueous solution having foaming properties to elute at least a part of the resin content of the treated product. In particular, since the alkaline aqueous solution has foaming properties, in addition to the resin content removal effect by the alkali, the resin content can be physically peeled off and removed from the surface of the carbon fiber by the foaming action in the aqueous solution. Therefore, even with a low concentration alkaline aqueous solution, carbon fibers without resin residue can be recovered in a short time.
[0023] In the carbon fiber recovery method of the present embodiment, the alkaline aqueous solution contains at least one of an alkaline carbonate and an alkaline hydrogen carbonate, and therefore, in addition to the effect of removing the resin by the alkali, the resin can be physically peeled off and removed from the surface of the carbon fiber by the foaming action in the aqueous solution. Therefore, even if the alkaline aqueous solution has a low concentration, carbon fiber without any resin residue can be recovered in a short time.
[0024] In addition, in the carbon fiber recovery method of the present embodiment, since the alkaline aqueous solution contains a foaming agent, the foaming action of the alkaline aqueous solution can be further promoted.
[0025] In addition, in the carbon fiber recovery method of this embodiment, the foaming agent contains at least one of a nonionic surfactant and an anionic surfactant, which can further promote the foaming action of the alkaline aqueous solution.
[0026] Furthermore, in the carbon fiber recovery method of this embodiment, the anionic surfactant contains at least one of a carboxylate, a sulfonate, a sulfate ester, and a phosphate ester, and the nonionic surfactant contains at least one of a polyhydric alcohol, so that the foaming action of the alkaline aqueous solution can be further promoted.
[0027] In the carbon fiber recovery method of the present embodiment, the foamable alkaline aqueous solution is a sodium carbonate aqueous solution or a sodium bicarbonate aqueous solution having a concentration of 0.005 to 0.1 M, and therefore in addition to the resin removal effect of the alkali, the foaming action in the aqueous solution has the effect of physically peeling and removing the resin from the surface of the carbon fiber. Therefore, even with a low-concentration alkaline aqueous solution, carbon fibers without any resin residue can be recovered in a short time.
[0028] Furthermore, in the carbon fiber recovery method of this embodiment, in the first treatment step, the carbon fiber reinforced plastic is immersed in an aqueous nitric acid solution having a temperature of 60 to 80°C and a concentration of 4 to 8 M for 8 hours or more, so that carbon fibers without resin residue can be recovered.
[0029] Furthermore, in the carbon fiber recovery method of the present embodiment, in the second treatment step, the treated material from the first treatment step is immersed in the aqueous sodium carbonate solution or the aqueous sodium hydrogen carbonate solution at a temperature of 60 to 80°C for 1 to 120 minutes, so that carbon fibers free of resin residues can be recovered in a short period of time.
[0030] In the method for producing carbon fiber reinforced plastic according to the present embodiment, recycled carbon fibers recovered by the above carbon fiber recovery method are used to produce carbon fiber reinforced plastic, and therefore the mechanical properties such as tensile strength are higher than those of virgin carbon fibers, making it possible to obtain carbon fiber reinforced plastic with higher bending strength, tensile strength, and interfacial shear strength than carbon fiber reinforced plastic using virgin carbon fibers. EXAMPLES
[0031] The present invention will be described below with reference to more specific examples. However, the numerical values and conditions shown below are not intended to limit the technical scope of the present invention in any way.
[0032] (A) Sample preparation As shown in FIG. 1A, discarded carbon fiber reinforced plastic parts for automobiles impregnated with epoxy resin were cut into pieces measuring 50 mm x 50 mm, and used as carbon fiber reinforced plastic samples (hereinafter referred to as CFRP samples).
[0033] (B) Method for recovering recycled carbon fiber As shown in FIG. 1B, the CFRP sample was immersed in an aqueous nitric acid solution (HNO3) adjusted to a concentration of 8 M for 8 to 48 hours (8 hours, 9 hours, 12 hours, 24 hours, and 48 hours) in an environment at 80°C. Then, as shown in FIG. 1D, the sample was removed from the test tube, washed with pure water, and dried in an environment at 80°C for 48 hours or more to obtain recycled carbon fibers according to Comparative Examples 1 to 5.
[0034] As shown in FIG. 1B, the CFRP sample was immersed in a nitric acid aqueous solution (HNO3) adjusted to a concentration of 8M for 8 hours in an environment at 80°C, and then the sample was taken out of the test tube and washed with pure water until the acidic aqueous solution could be removed, as shown in FIG. 1C. Then, as shown in FIG. 1C, the washed sample was immersed in a sodium bicarbonate aqueous solution (NaHCO3) adjusted to a concentration of 0.01 to 0.1M (0.01M, 0.1M) for 1 to 90 minutes (1 minute, 5 minutes, 10 minutes, 15 minutes, 20 minutes, 30 minutes, 90 minutes) in an environment at 80°C, and then the sample was taken out. The taken-out sample was washed with pure water and dried in an environment at 80°C for 48 hours or more, as shown in FIG. 1D, to obtain the recycled carbon fibers according to Examples 1 to 7.
[0035] For comparative evaluation with Examples 1 to 7, instead of the aqueous sodium bicarbonate solution (NaHCO3) shown in FIG. 1C, a 1.0×10 -6 The samples were immersed in an aqueous sodium hydroxide solution (NaOH) adjusted to M for 1 to 60 minutes (1 minute, 10 minutes, 20 minutes, 60 minutes) in an environment of 80°C, and then removed. As shown in Fig. 1D, the removed samples were washed with pure water and dried in an environment of 80°C for 48 hours or more to obtain recycled carbon fibers according to Comparative Examples 6 to 9.
[0036] As shown in FIG. 1B, the CFRP sample was immersed in a nitric acid aqueous solution (HNO3) adjusted to a concentration of 8M for 8 hours in an environment at 80°C, and then the sample was taken out of the test tube and washed with pure water until the acidic aqueous solution could be removed, as shown in FIG. 1C. Then, as shown in FIG. 1C, an alkaline aqueous solution was prepared using sodium bicarbonate aqueous solution (NaHCO3) as an alkaline aqueous solution, sodium lauryl sulfate (SDS) as a surfactant, polyethylene glycol (PEG) with molecular weights of 200 and 600, sodium lauryl sulfate, and polyethylene glycol with molecular weight of 200 as a foaming agent. The concentration of the sodium bicarbonate aqueous solution was adjusted to 0.01M, and the concentration of the surfactant as a foaming agent was adjusted to 0.1% by weight to 1% by weight (0.1% by weight, 1.0% by weight). Then, as shown in FIG. 1C, the sample was immersed in this alkaline aqueous solution, and after immersing for 10 to 60 minutes (10 minutes, 60 minutes) in an environment at 80°C, the sample was taken out. The taken-out sample was washed with pure water as shown in FIG. 1D, and then dried in an environment of 80° C. for 48 hours or more, thereby obtaining the recycled carbon fibers according to Examples 8 to 15.
[0037] As shown in Fig. 1B, the CFRP sample was immersed in an aqueous solution of nitric acid (HNO3) adjusted to a concentration of 8M for 8 hours in an environment at 80°C, and then the sample was taken out of the test tube and washed with pure water until the acidic aqueous solution could be removed, as shown in Fig. 1C. Then, using a surfactant sodium lauryl sulfate (SDS) as a foaming agent, aqueous solutions adjusted to concentrations of 0.1% and 0.3% were prepared, and the sample was immersed in an environment at 80°C for 20 minutes and then taken out. The removed sample was washed with pure water as shown in Fig. 1D, and then dried in an environment at 80°C for 48 hours or more to obtain recycled carbon fibers according to Comparative Examples 10 to 11.
[0038] (C) Evaluation of resin decomposition rate from recycled carbon fiber (C-1) Evaluation Method A CFRP sample was immersed in each of the above-mentioned solutions, and the change in the resin decomposition rate Rd (mass%) of the obtained recycled carbon fiber with time was calculated using the following formula 1.
number
[0039] The mass fraction (Fm) of the resin impregnated in the CFRP sample was experimentally determined by heat treating the CFRP sample and measuring the change in the mass of the sample before and after thermal decomposition. As a result, the mass of the CFRP sample before heating was 1.2772g, whereas the mass of the CFRP after heating decreased to 0.7692g. From these results, Fm = (1 - 0.7692 ÷ 1.2772) × 100 = 39.77% was determined. Furthermore, this experiment was repeated multiple times, confirming that Fm = 40.0%.
[0040] (C-2) Evaluation results and considerations For each of the samples of Examples 1 to 15 and Comparative Examples 1 to 11, the change in the resin decomposition rate with time was calculated using the above formula 1. The results are shown in Table 1.
[0041] [Table 1]
[0042] In Comparative Examples 1 to 5, after immersion in the nitric acid aqueous solution for 8 hours, Rd was 75.8 mass%, after 12 hours, Rd was 89.1 mass%, after 24 hours, Rd was 94.9 mass%, and after 48 hours, Rd was 95.3 mass%. Since there was almost no change in the resin decomposition rate after 24 hours, it is believed that most of the resin was decomposed within 24 hours.
[0043] In Examples 1 to 7, after immersion in an aqueous nitric acid solution for 8 hours, immersion in a 0.1 M aqueous sodium hydrogen carbonate solution for 15 minutes showed Rd=96.4 mass%. When the concentration of the aqueous sodium hydrogen carbonate solution was decreased to 0.05 M and 0.01 M, immersion for about 60 minutes at 0.05 M and about 90 minutes at 0.01 M showed Rd=95 mass% or more.
[0044] On the other hand, in Comparative Examples 6 to 9, which used an aqueous sodium hydroxide solution, even though they were both weakly alkaline solutions, the resin decomposition was slow, and it took more than 20 minutes for Rd to reach 95 mass% or more. According to the comparison results between Examples 1 to 7 and Comparative Examples 6 to 9, it is believed that in Examples 1 to 7, in addition to dissolving the resin with an alkali, the aqueous sodium hydrogen carbonate solution foams in an environment of 80°C, physically peeling off the resin, making it possible to remove the resin in a short time.
[0045] Furthermore, a comparison between Comparative Examples 1 to 5 and Examples 1 to 7 showed that in Examples 1 to 7, recycled carbon fibers with no resin residue and an Rd of 95 mass% were obtained in about 8.2 to 9.5 hours, demonstrating that this is a method that can significantly shorten the recovery time.
[0046] In Examples 8 to 15, it was confirmed that by using an aqueous sodium bicarbonate solution in combination with a foaming agent (a surfactant such as sodium lauryl sulfate (SDS) or polyethylene glycol), Rd = 95 mass% or more was achieved in a short period of time even under conditions of a low concentration aqueous sodium bicarbonate solution such as 0.01 M.
[0047] In addition, in Comparative Examples 10 to 11, the resin decomposition rate did not increase significantly, which indicated that a foaming agent such as a surfactant alone without an alkaline aqueous solution does not effectively decompose and remove resin in a short period of time.
[0048] (D) Surface observation of virgin carbon fiber (vCF) and recycled carbon fiber (rCF) The results of observing the surfaces of virgin carbon fiber (hereinafter also referred to as vCF) and recycled carbon fiber (hereinafter also referred to as rCF) with a scanning electron microscope (SEM) are shown in Figs. 2A to 2C.
[0049] FIG. 2A is a scanning electron microscope photograph showing the regenerated carbon fiber according to Comparative Example 1, which was immersed in a nitric acid aqueous solution for 8 hours and then recovered, and resin residue was confirmed on the carbon fiber surface. FIG. 2B is a scanning electron microscope photograph showing the regenerated carbon fiber according to Example 4, which was immersed in a nitric acid aqueous solution for 8 hours and then immersed in a 0.1M sodium bicarbonate aqueous solution for 15 minutes and then recovered, and clean carbon fiber without resin residue was recovered. FIG. 2C is a scanning electron microscope photograph showing the regenerated carbon fiber according to Example 10, which was immersed in a nitric acid aqueous solution for 8 hours and then immersed in a 0.01M low-concentration sodium bicarbonate aqueous solution to which 1.0% by weight of sodium lauryl sulfate was added, and then recovered for 10 minutes, and clean carbon fiber without resin residue was recovered, despite the low-concentration alkaline aqueous solution and the short time.
[0050] (E) Method for producing carbon fiber reinforced plastic (rCFRP) using recycled carbon fibers A dry nonwoven fabric was produced using the recycled carbon fiber according to Example 4 described above. For comparative evaluation, a dry nonwoven fabric was also produced using virgin carbon fiber. Each of the produced nonwoven fabrics was set in a 250×200 mm mold and impregnated with epoxy resin under conditions of a mold temperature of 120° C., a molding pressure of 20 t, and a curing time of 5 minutes, to produce a CFRP molded plate made of recycled carbon fiber (hereinafter also referred to as rCFRP) and a CFRP molded plate made of virgin carbon fiber (hereinafter also referred to as vCFRP).
[0051] (F) CFRP three-point bending test (F-1) Evaluation Method A three-point bending test was conducted based on JIS K 7074-1988 (Bending test method for carbon fiber reinforced plastics) to evaluate the bending strength and bending modulus. For the three-point bending test, a test piece with a length of 100 mm and a width of 15 mm was cut out from a CFRP molded plate with a size of 250 x 200 mm, and the test was conducted at a bending speed of 5 mm / min. The evaluation results of the three-point bending test are shown in Figure 3. The vertical axis of the left graph in Figure 3 shows bending strength (MPa), and the vertical axis of the right graph in Figure 3 shows bending modulus (GPa).
[0052] (F-2) Evaluation Results As shown in Figure 3, vCFRP had a bending strength of 391 ± 32 MPa and a bending modulus of 23.3 ± 1.7 GPa, while rCFRP had a bending strength of 418 ± 16 MPa and a bending modulus of 27.1 ± 1.2 GPa. It was confirmed that the bending strength of rCFRP was 1.1 times that of vCFRP, and the bending modulus of rCFRP was 1.2 times that of vCFRP.
[0053] (G) Tensile test of CFRP (G-1) Evaluation Method A tensile test was conducted based on JIS K 7083-1993 (constant load tensile test of carbon fiber reinforced plastics) to evaluate the tensile strength and tensile modulus. For the tensile test, a test piece 200 mm long and 25 mm wide was cut out from a CFRP plate measuring 250 x 200 mm, and the test was conducted at a tensile speed of 2 mm / min. The evaluation results of the tensile test are shown in Figure 4. The vertical axis of the left graph in Figure 4 shows the tensile strength (MPa), and the vertical axis of the right graph in Figure 3 shows the tensile modulus (GPa).
[0054] (G-2) Evaluation Results As shown in Figure 4, vCFRP had a tensile strength of 248 ± 59 MPa and a tensile modulus of 26.9 ± 4.2 GPa, while rCFRP had a tensile strength of 258 ± 35 MPa and a tensile modulus of 35.8 ± 2.7 GPa. It was confirmed that the tensile strength of rCFRP was approximately the same as that of vCFRP, and that the tensile modulus of rCFRP was about 1.3 times that of vCFRP.
[0055] (H) Evaluate the quality of a single fiber To evaluate the quality of single fibers, we performed a microdroplet test to measure the interfacial shear strength between the fiber and resin, a single fiber strength test, X-ray photoelectron spectroscopy (XPS) measurement, and observation evaluation of the cross section of the carbon fiber using energy dispersive X-ray spectroscopy (TEM-EDX). Two types of carbon fibers were evaluated: vCF and rCF. The rCF used was the recycled carbon fiber recovered in Example 4.
[0056] (I) Microdroplet test (I-1) Evaluation method The adhesion between the carbon fiber and the epoxy resin was evaluated by performing a microdroplet test on vCF and rCF. The single fiber pull-out speed in the microdroplet test was 0.12 mm / min, and the maximum load F (mN) when the resin ball was pulled out was measured, and the interfacial shear strength τ (MPa) was calculated using the following formula 2.
number
[0057] Since it has been reported that there is a positive correlation between the interfacial shear strength τ and the diameter L of the resin beads, the τ values obtained in the measurements were plotted against the diameter L of the resin beads used in the measurements, a linear regression equation was obtained, and the interfacial shear strength τ corresponding to a resin bead of 70 μm was calculated, thereby calculating the interfacial shear strength value for resin beads of the same size. Figure 5 shows the evaluation results of the interfacial shear strength by the microdroplet test. The vertical axis of Figure 5 shows the interfacial shear strength (MPa).
[0058] (H-2) Evaluation Results As shown in Figure 5, the interfacial shear strength of vCF was τ = 30 ± 3.1 MPa, while that of rCF was τ = 82 ± 8.6 MPa, confirming that the interfacial shear strength of rCF was 2.7 times higher than that of vCF.
[0059] (J) Quantification of the amount of functional groups on the carbon fiber surface by X-ray photoelectron spectroscopy (XPS) measurement Elemental analysis was performed using X-ray photoelectron spectroscopy (XPS), and the composition ratio of functional groups contained in each sample was calculated. The results are shown in Table 2. Among these functional groups, the functional groups involved in the bond with the resin are shown in gray hatching in Table 2 (C-OH, COC, >C=O, -CO-O-, -NH2, ―NO / NH4, -NO2, O). The results of calculating the abundance ratio of these functional groups involved in the bond with the resin are shown in the bottom row of Table 2. In vCF, the abundance of functional groups involved in the bond with the resin was 52.2%, while in rCF, the abundance of functional groups involved in the bond with the resin was 63.2%, confirming that the abundance of functional groups involved in the bond with the resin increased in rCF. A correlation was found between the abundance of functional groups involved in the bond with the resin and the value of the interfacial shear strength with the resin shown in Figure 5, indicating that functional groups derived from nitric acid were added to the carbon fiber surface during the carbon fiber recovery process.
[0060] [Table 2]
[0061] (K) Carbon fiber tensile test (K-1) Evaluation Method Tensile tests on vCF and rCF single fibers were carried out based on JIS R 7606 (Testing method for tensile properties of carbon fibers - short fibers). Both ends of each single fiber sample were pulled at a tensile speed of 1 mm / min, and the maximum load F' (mN) measured by the testing machine when the single fiber broke was recorded, and the tensile strength σ (GPa) was evaluated using the following formula 3.
number
[0062] (K-2) Evaluation Results The tensile strength of the single fiber was σ = 0.75 ± 0.007 GPa for vCF, whereas it was σ = 1.26 ± 0.089 GPa for rCF. The variance in the tensile strength values was calculated as the standard deviation when approximating the Weibull distribution. Similar to the phenomenon observed for the interfacial shear strength between the fiber and the resin, the tensile strength of the single fiber of rCF was 1.7 times higher than that of vCF.
[0063] (L) Observation of carbon fiber cross section (L-1) Evaluation method To observe the cross-sections of the carbon fibers, cross-sections with a thickness of about 100 nm were prepared using focused ion beam (FIB) processing. The prepared cross-sections were observed using a transmission electron microscope (TEM), and the element distribution in the cross-section was observed using an energy dispersive X-ray spectrometer (EDX). Figure 7 shows the results of TEM observation of the carbon fiber cross-sections. The upper left of Figure 7 shows a TEM photograph of vCF, and the lower left shows an enlarged photograph of part VIIA. The upper right of Figure 7 shows a TEM photograph of rCF, and the lower right shows an enlarged photograph of part VIIB.
[0064] (L-2) Evaluation results From the TEM observation results of vCF shown in Figure 7, voids were confirmed in the region 400 nm inside from the carbon fiber surface, and their size was about 1 to 30 nm. In contrast, looking at the TEM observation results of rCF, the amount of voids was smaller than in vCF, and the region where the voids existed was also 50 nm inside from the surface, which was the extreme surface layer compared to vCF.
[0065] Table 3 shows the results of quantifying the proportion of voids in the cross-section of the observed carbon fiber using image analysis software Image J. As a result, it was shown that the amount of voids in rCF (0.73%) was reduced to less than one-third of the amount of voids in vCF (3.21%). This is thought to be because the graphite structure of the surface layer was removed by the nitric acid in the first treatment process.
[0066] [Table 3]
[0067] Next, FIG. 8 shows the results of EDX mapping of the observed voids with C (carbon), N (nitrogen), and O (oxygen) as target elements. In the EDX mapping image, voids where no elements are present are shown in black, but as shown in FIG. 8, not only C (carbon) but also N (nitrogen) and O (oxygen) were not confirmed in the voids (black parts) of vCF. In contrast, C (carbon) was not confirmed in the voids of rCF, as in vCF, but O (oxygen) was confirmed to be present in the voids in a dense manner. That is, in the EDX mapping image of rCF in FIG. 8 with C element as the target element, three large circular black areas where C element is not present are observed in the upper left part indicated by the dashed circle. In contrast, in the EDX mapping image of the same field of view with O element as the target element, the color indicating O element is observed to be dark in the same position indicated by the dashed circle. This indicates that O element is present in a dense manner in this part, and oxygen is present in the voids.
[0068] From the results of the cross-sectional observation of carbon fibers, the following two factors can be cited as reasons why the tensile strength of recycled carbon fibers is improved compared to virgin carbon fibers. First, the amount of voids present in rCF is reduced. It is known that carbon fibers are brittle materials, and their strength is greatly affected by defects on the surface and inside the fiber. Also, previous reports have confirmed that the smaller the diameter of the voids inside the fiber, the higher the fiber strength. Therefore, in fibers with improved tensile strength, it is believed that the reduced amount of voids present reduces the number of starting points for stress concentration when a tensile load is applied, leading to improved tensile strength.
[0069] Secondly, functional groups containing at least either oxygen or nitrogen were incorporated into the voids, which reduced the number of starting points when a tensile load was applied to the carbon fiber, resulting in improved tensile strength compared to virgin carbon fiber that had not been treated in any way.
[0070] (M) Evaluation of the graphite structure of carbon fibers (M-1) Evaluation Method Raman spectroscopy was performed, and the areas of the G1 and D1 peaks in the obtained Raman spectrum were calculated. The G1 peak represents a peak derived from a six-membered carbon ring structure (high crystallinity), and the D1 peak represents a peak derived from structural disorder (low crystallinity) such as partial cleavage of the six-membered carbon ring. Therefore, the graphite structure was evaluated by calculating the peak area ratio of D1 / G1. The results are shown in FIG. 9. The vertical axis of FIG. 9 represents the peak area ratio of D1 / G1.
[0071] (M-2) Evaluation Results As shown in Figure 9, the peak area ratio of rCF did not change significantly relative to that of vCF, indicating that there was no disruption of the graphite structure or a decrease in crystallinity due to recycling.
Claims
1. A first treatment step of immersing a carbon fiber reinforced plastic in an acidic aqueous solution to dissolve at least a part of the resin content of the carbon fiber reinforced plastic; a second treatment step of immersing the treated material in a foaming alkaline aqueous solution to dissolve at least a portion of the resin content of the treated material.
2. The method for recovering carbon fibers according to claim 1 , wherein the alkaline aqueous solution contains at least one of an alkaline carbonate and an alkaline hydrogen carbonate.
3. The method for recovering carbon fibers according to claim 1 , wherein the alkaline aqueous solution contains a foaming agent.
4. The method for recovering carbon fibers according to claim 3 , wherein the foaming agent contains at least one of a nonionic surfactant and an anionic surfactant.
5. The anionic surfactant includes at least one of a carboxylate, a sulfonate, a sulfate, and a phosphate, The method for recovering carbon fibers according to claim 4 , wherein the nonionic surfactant contains at least one polyhydric alcohol.
6. The carbon fiber recovery method according to any one of claims 1 to 5, wherein the alkaline aqueous solution is an aqueous sodium carbonate solution or an aqueous sodium bicarbonate solution having a concentration of 0.005 to 0.1 M.
7. 7. The method for recovering carbon fibers according to claim 6, wherein in the first treatment step, the carbon fiber reinforced plastic is immersed in an aqueous nitric acid solution having a temperature of 60 to 80° C. and a concentration of 4 to 8 M for 8 hours or more.
8. 7. The carbon fiber recovery method according to claim 6, wherein in the second treatment step, the treated product treated in the first treatment step is immersed in the aqueous sodium carbonate solution or the aqueous sodium hydrogen carbonate solution having a temperature of 60 to 80° C. for 1 to 120 minutes.
9. A method for producing carbon fiber reinforced plastics using recycled carbon fibers recovered by the method for recovering carbon fibers according to any one of claims 1 to 5.
Citation Information
Patent Citations
Method of manufacturing carbon fiber and carbon fiber reinforced resin composition
JP2019136932A